2015
DOI: 10.1128/aac.04283-14
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of β-Lactam Action in Streptococcus pneumoniae: the Piperacillin Paradox

Abstract: fThe human pathogen Streptococcus pneumoniae has been treated for decades with ␤-lactam antibiotics. Its resistance is now widespread, mediated by the expression of mosaic variants of the target enzymes, the penicillin-binding proteins (PBPs). Understanding the mode of action of ␤-lactams, not only in molecular detail but also in their physiological consequences, will be crucial to improving these drugs and any counterresistances. In this work, we investigate the piperacillin paradox, by which this ␤-lactam se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
(69 reference statements)
2
21
0
Order By: Relevance
“…With cefotaxime, R6-PBP2b is 4 ϫ 10 7 -fold less reactive than PBP2x (9). Qualitatively, the reactivities measured in vitro here and in other studies for R6 PBPs (9,10,14) are in agreement with the acylations observed in vivo (18,26).…”
supporting
confidence: 78%
See 2 more Smart Citations
“…With cefotaxime, R6-PBP2b is 4 ϫ 10 7 -fold less reactive than PBP2x (9). Qualitatively, the reactivities measured in vitro here and in other studies for R6 PBPs (9,10,14) are in agreement with the acylations observed in vivo (18,26).…”
supporting
confidence: 78%
“…ments (12,18,22). Note that if the c 50 is considered, 5204-PBP2b is slightly less susceptible to ␤-lactam than HybridPBP2b.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We report here that direct inhibition studies confirm previous findings that cefotaxime and piperacillin are coselective for PBP3 and PBP2x and that piperacillin does possess a partial relative affinity for PBP2b in our assay. Importantly, a recent study confirmed this piperacillin inhibition profile and also provided compelling evidence that PBP2b is a critical target of this drug and that combined inhibition of PBP2x and PBP2b may be key to the unusual resistance pattern seen with this molecule (43).…”
Section: Fig 3 Representative Graphs Showing the Inhibition Of Pbps Wmentioning
confidence: 54%
“…Recently, PBP2x seems to have been the primary target for piperacillin and not PBP2b [19]. Another recent genomewide association study identified a set of 301 single nucleotide polymorphisms, from which 73 caused amino acid alterations in cell-wall synthesis genes [20].…”
Section: Beta-lactam Resistancementioning
confidence: 99%